Behaviour of CFRP jacketed HSS tubular members under compression – an experimental investigation - Sundarraja, M.C.; Sivasankar, S. (Journal of Structural Engineering, 2024)
Hollow structural steel (HSS) tubular structures possess excellent earthquake-resistant properties such as high strength, high ductility, and large energy absorption capacity. In the last decades, they have gained increasing popularity in buildings, bridges and other structural applications. They have proven to be economical as well, providing for rapid construction and saving of additional costs from elimination of formwork, while also being labour saving. Due to deterioration and aging of these tubular structures in the construction industry, the repairing/strengthening/retrofitting of above structures has become very essential. Fibre reinforced polymer (FRP) composites have been used widely for the repair of concrete elements, but their application to steel structures has been so far minimal. This paper presents axial strengthening of hollow square steel tubes using externally bonded carbon fibre reinforced polymer (CFRP) fabrics. Totally fourteen HSS tubes were used for axial compression testing. Among fourteen specimens, two specimens were used as control and twelve were wrapped with horizontal CFRP strips. The main parameters were spacing of FRP strips and number of layers. Experiments were carried out until failure and influence of FRP characteristics on the behaviour of hollow square steel tubular sections including their failure modes, stress-strain behaviour, enhancement in load carrying capacity and ductility index were studied. Finally, the behaviour of externally bonded hollow tubular sections was compared with one another and also with the control specimens. From the test results it is found that CFRP strengthening significantly increases the axial stress-strain and load carrying capacity of the HSS members.